Astronomical seeing and wind speed distributions with ERA5 data at Lenghu site on the Tibetan Plateau. Issue 1 (6th April 2023) - Zhu, Liming; Zhang, Hanjiu; Sun, Gang; Li, Xuebin; Yang, Fan; He, Fei; Weng, Ningquan; Deng, Licai
ABSTRACT: In this paper, we present comprehensive night-time seeing statistics at the Lenghu site using data collected between 2018 and 2021 using a differential image motion monitor. The results show that the median seeing is 0.80 arcsec, which slightly larger than that previously reported due to climate change. Additionally, we investigated the annual, seasonal, and monthly seeing statistics, as well as possible hourly seeing trends in each season. The results demonstrate that the seeing at the Lenghu site is very stable, with monthly median seeing varying from 0.6 to 0.95 arcsec. The seasonal dependence of seeing shows obvious variations over different years. The best year of seeing was 2019 (0.74 arcsec), and the best seeing occurred in spring (0.68 arcsec) to early summer (June, 0.63 arcsec), while the worst seeing occurred in winter (0.80 arcsec). The minimum seeing value throughout the night is at approximately three hours before dawn. Furthermore, wind speed profiles, especially V 200 (particularly the wind speed at 200 mbar), are important parameters for evaluating astronomical sites in terms of their suitability for adaptive optics. We first show the complete monthly average behaviours of the wind speed profile and V 200 using the European Center for Medium-Range Weather Forecast reanalysis data sets. The results demonstrate the annual periodicity and variability of V 200, and the yearly V 200 modulation function is also provided. V 200 maintains large values throughout the autumn (average: 35.01 m s −1 ) and winter (average: 34.33 m s −1 ), while the minimum V 200 occurs in spring (average: 27.93 m s −1 ).